Draft Outline of the Fourth Five Year Plan (1969—74) [The draft incorporates the proposals for the Annual Plan 1969-70] Government of Bihar - Planning Commission (Planning Commission, 1968)
The draft outline gives the substance of the proposals of the State Government of Bihar for the Fourth Five Year Plan (1969—74). With minor modifications the draft is according to the format suggested in Planning Commission letter no. PC(P)1/4(1)66., dated the 27th July, 1968. The proposals contained in this first draft will be discussed in the Working Groups consisting of officers from the Planning Commission, representatives of the Central Ministries and of the State Government in October, 1968. the final draft will emerge after the discussions with Planning Commission have been completed.